At the water's edge: Micromorphological and quantitative mineral analysis of a submerged Mesolithic shell midden at Hjarnø Sund, Denmark. (February 2019) - Ward, Ingrid; Moe-Astrup, Peter; Merigot, Kelly
Abstract: This study presents the first application of micromorphology and Automated Scanning Electron Microscopy (ASEM) to a submerged shell-bearing midden site in Denmark, one of the few submerged shell-matrix sites in the world to have undergone archaeological excavation. The use of micromorphology in these deposits provides a means to distinguish primary and secondary deposits and degree of preservation. The additional input of quantitative mineral analysis provides an empirical tool for correlation of minerogenic components across the site and assessing change through time. Micromorphological insights into the formation history and post-depositional modification include epizootic infestations within oyster shells at the base of the profile and needle-fibre calcite at the top - the former is indicative of accumulation of at least part of the shell midden below water, whilst the latter is indicative of exposure. Aside from the shell itself, other cultural traces include heated and worked flint fragments, burnt and unburnt hard bone fragments (including fish bone), soft (spongy) bone, charcoal ( Ulmus sp., Alnus sp., Corylus sp.), and preservation of what could possibly be antler velvet. Quantitative mineral analyses provide support for the successive stabilisation of the midden site by accumulating minerogenic (silica-rich) sands over the glacial clay and detrital gyttja deposits (defined by smaller grain size, greater heavy mineral content), and subsequently between the shell matrix itself, until the erosion of these protective sediments in more recent times. Further micromorphological profiles are needed to fully assess local versus regional signatures within the site, which otherwise provides an ideal context against which to compare the effects of inundation in similar microtidal contexts.